Rethinking food crisis responses: Nigeria launch of the CGIAR Initiative on Fragility, Conflict, and Migration - Onilogbo, Omobolanle; Fasoranti, Adetunji; Carrillo, Lucia; Kosec, Katrina; Andam, Kwaw S.; Edeh, Hyacinth O.; Anisimova, Evgeniya (CGIAR, 2023)
On May 11, 2023 the Abuja office of the International Food Policy Research Institute (IFPRI Nigeria) and the CGIAR Research Initiative on Fragility, Conflict, and Migration (FCM) co-hosted a hybrid event featuring the Nigeria presentation of IFPRI’s 2023 Global Food Policy Report (GFPR) titled “Rethinking Food Crises Responses” and the launch of the FCM Initiative. The event drew together various stakeholders in the agricultural policy space who reflected on the report and the research initiative plans and their relevance for diverse issues currently confronting Nigeria in the areas of food crises, fragility, conflict, and migration.